ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN SISTEM DU PONT PADA PT. PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN(UP3) PAREPARE - M, Nurwani; Wardhani, Wardhani; Arodhiskara, Yadi (Universitas Muhammadiyah Parepare, 2021)
The financial report is the result of the act of making a summary of financial data. The financial statement is the result of the act of making a summary of financial data. Financial statements issued by the company are one of the sources of information regarding the company's financial position, performance, and changes in the company's financial position that are useful to support the right decision-making. The performance of a company, both financial performance and other performance, of course, depends on the company's operations. The aim of this research was to determine the company's financial performance by using the du pont system at PT. PLN (PERSERO) of customer service implementation Unit in Parepare for the last five years (2015-2019). This research was conducted at PT. PLN (PERSERO) of customer service implementation Unit in Parepare for 3 months starting from May to July 2021. This research used a method to analyze company performance with du pont system (ROI with a Du Pont approach). The results of the research proved the financial performance at PT. PLN (Persero) of the customer service implementation Unit in Parepare is in good condition viewed from the NPM, while it is in poor condition viewed from the TATO, then if it is viewed from the ROI, the company's financial performance is in good condition. Therefore, it concludes that the financial performance at PT. PLN (Persero) of the Customer Service Implementation Unit in Parepare is in good condition, although the TATO value shows an unfavorable value. However, the ROI value is still in accordance with the standard because it is balanced with the NPM value which is always increasing.